Mental health and wellbeing in the legal profession - Jones, Emma (Law teacher); Graffin, Neil; Samra, Rajvinder; Lucassen, Mathijs, 1975- (Bristol : Bristol University Press, 2021)
This exploration of mental health and wellbeing in the UK and Republic of Ireland's legal sector is a timely addition to international debates on the topic. It uses qualitative research to explore how cultural or structural factors impact practitioners, the legal profession, and wider society, suggesting interventions to improve wellbeing.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on April 30, 2021).
Keywords: Lawyers -- Mental health -- Great Britain; Lawyers -- Mental health -- Ireland; Law; Jurisprudence & general issues